Prediction of machining-induced phase transformation and grain growth of Ti-6Al-4 V alloy. Issue 1 (October 2016) - Pan, Zhipeng; Liang, Steven; Garmestani, Hamid; Shih, Donald
Abstract The high-speed machining process can significantly influence the microstructure of the machined surface in titanium alloy. A physics-based finite element method is proposed for the modeling of machining-induced phase transformation and grain size growth of Ti-6Al-4 V material. Prediction of the grain growth and phase transformation are obtained with the Johnson-Mehl-Avrami-Kolmogorov (JMAK) dynamic recrystallization model and Avrami model, respectively. A modified Johnson Cook flow stress model is embedded into the method to account for the phase transformation. The accuracy of the proposed method is validated with experimental data. Parametric studies are conducted to investigate the effects of the cutting speed and the feed rate on the microstructure change in machining.